The sources of growth at different levels of development - Evan Osborne (Osaka University, Institute of Social and Economic Research (ISER), 2003)
Cross-country growth regressions have become an increasingly common tool in empirical development research. But these regressions typically do not attempt to distinguish among countries in different stages of development. Two empirical methods are used to test for such differences. Several of the factors known to affect economic growth are shown to operate differently for countries in different portions of the global income distribution. The results have implications for the role of financial markets, openness and human capital in promoting growth.
Keywords: 330; Wachstumspolitik; Wirtschaftswachstum; Institutionelle Infrastruktur; Wirkungsanalyse; Nationaleinkommen; Welt